Pengaruh Kualitas Layanan dan Harga Terhadap Kepuasan Konsumen: (Studi Pada Pengguna Layanan Prabayar Simpati Telkomsel di Kabupaten Bantaeng) - Novarianti Novarianti; Muhammad Ichwan Musa; Burhanuddin Burhanuddin; Chalid Imran Musa; Ilma Wulansari Hasdiansa (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to analyze the influence of service quality and price on consumer satisfaction. This research was conducted in Bantaeng Regency. The population in this research is an unlimited population, namely consumers who have used Simpati Telkomsel prepaid services. The sample in this research was 50 respondents. This research is explanatory quantitative research. The results of this research show that service quality does not partially have a positive and significant effect on consumer satisfaction with a significant value of 0.345 > 0.05 and price partially has a positive and significant effect on consumer satisfaction with a significant value of 0.000 < 0.05. This shows that prices that are increasingly in line with consumer perceptions will increase consumer satisfaction and the prices set by Simpati Telkomsel can be competitive with other competitors and customers also feel that the costs they have to pay are in line with the benefits obtained.